"Education just a game when you can play Indians [sic] or Eskimos [sic] with Museum exhibits" (Philadelphia Evening Bulletin, 1942)
Visitors at the University of Pennsylvania Museum of Archaeology inspect a model of a Malayan hut and Siamese river boat. Title from clipping caption